Incidence, aetiology, and sequelae of viral meningitis in UK adults: a multicentre prospective observational cohort study. Issue 9 (September 2018) - McGill, Fiona; Griffiths, Michael J; Bonnett, Laura J; Geretti, Anna Maria; Michael, Benedict D; Beeching, Nicholas J; McKee, David; Scarlett, Paula; Hart, Ian J; Mutton, Kenneth J; Jung, Agam; Adan, Guleed; et al.
Summary: Background: Viral meningitis is increasingly recognised, but little is known about the frequency with which it occurs, or the causes and outcomes in the UK. We aimed to determine the incidence, causes, and sequelae in UK adults to improve the management of patients and assist in health service planning. Methods: We did a multicentre prospective observational cohort study of adults with suspected meningitis at 42 hospitals across England. Nested within this study, in the National Health Service (NHS) northwest region (now part of NHS England North), was an epidemiological study. Patients were eligible if they were aged 16 years or older, had clinically suspected meningitis, and either underwent a lumbar puncture or, if lumbar puncture was contraindicated, had clinically suspected meningitis and an appropriate pathogen identified either in blood culture or on blood PCR. Individuals with ventricular devices were excluded. We calculated the incidence of viral meningitis using data from patients from the northwest region only and used these data to estimate the population-standardised number of cases in the UK. Patients self-reported quality-of-life and neuropsychological outcomes, using the EuroQol EQ-5D-3L, the 36-Item Short Form Health Survey (SF-36), and the Aldenkamp and Baker neuropsychological assessment schedule, for 1 year after admission. Findings: 1126 patients were enrolled between Sept 30, 2011, and Sept 30, 2014. 638 (57%) patients had meningitis: 231 (36%) cases were viral, 99 (16%) were bacterial, and 267 (42%) had an unknown cause. 41 (6%) cases had other causes. The estimated annual incidence of viral meningitis was 2·73 per 100 000 and that of bacterial meningitis was 1·24 per 100 000. The median length of hospital stay for patients with viral meningitis was 4 days (IQR 3–7), increasing to 9 days (6–12) in those treated with antivirals. Earlier lumbar puncture resulted in more patients having a specific cause identified than did those who had a delayed lumbar puncture. Compared with the age-matched UK population, patients with viral meningitis had a mean loss of 0·2 quality-adjusted life-years (SD 0·04) in that first year. Interpretation: Viruses are the most commonly identified cause of meningitis in UK adults, and lead to substantial long-term morbidity. Delays in getting a lumbar puncture and unnecessary treatment with antivirals were associated with longer hospital stays. Rapid diagnostics and rationalising treatments might reduce the burden of meningitis on health services. Funding: Meningitis Research Foundation and UK National Institute for Health Research.